Fibrinogen concentrations predict long‐term cognitive outcome in young ischemic stroke patients. Issue 2 (29th January 2018) - Pedersen, Annie; Stanne, Tara M.; Redfors, Petra; Viken, Jo; Samuelsson, Hans; Nilsson, Staffan; Jood, Katarina; Jern, Christina
Abstract: Essentials Cognitive impairment is frequent after stroke and knowledge on predictors is limited. We investigated hemostatic biomarkers as predictors of long‐term cognitive function after stroke. Fibrinogen, von Willebrand factor and tissue‐type plasminogen activator correlated to cognitive outcome. In young patients, fibrinogen was independently associated to worse cognitive outcome 7 years post‐stroke. Background: Cognitive impairment is frequent after stroke, and young patients may live with this consequence for a long time. Predictors of cognitive outcomes after stroke represent a current gap of knowledge. Objectives: To investigate levels of three hemostatic biomarkers as predictors of long‐term cognitive function after stroke. Methods: This longitudinal study included consecutively recruited patients with ischemic stroke at 18‐69 years (n = 268). Blood was collected 3 months after index stroke and analyzed for plasma concentrations of fibrinogen, von Willebrand factor (VWF) and tissue‐type plasminogen activator (t‐PA) antigen. Cognitive function 7 years after index stroke was assessed by the Barrow Neurological Institute Screen for Higher Cerebral Functions (BNIS). Participants with stroke <50 years of age were also examined by the Trail Making Test A and B (n = 41). Associations between biomarker concentrations and cognitive scales were assessed in the whole group and in participants with stroke <50 years of age. Results: The hemostatic biomarkers fibrinogen, VWF and t‐PA, were all correlated to total BNIS score, but these associations did not withstand adjustment for confounding factors in the whole group. However, in patients <50 years, we found an independent association between fibrinogen concentrations and total BNIS score (βstd = −.27, 95% confidence interval [CI], −0.47 to −0.07) and to performance on the Trail Making Test A (βstd = .31, 95% CI, 0.03–0.58). No such association was seen for the Trail Making Test B. Conclusion: High convalescent fibrinogen concentrations were associated with worse long‐term cognitive outcomes in ischemic stroke <50 years of age. We propose further investigations of fibrinogen in relation to cognitive function in stroke in the young.